To govern, or not to govern? Opportunity and post-coup military behaviour in Egypt 2011–2014. Issue 6 (18th August 2019) - Hoyle, Justin A.
ABSTRACT: This article examines Egyptian military behaviour in 2011 and 2013 to address the question of why officers remain in power following some successful coups, and allow for a transition to civilian rule after others. My evidence suggests that in post-1970 cases where international factors fail to exert sufficient pressure, outcome variation is influenced by levels of corporate opportunity, defined here as the ease with which the army can use control of the state to expand its corporate interests. Drawing on the existing literature, I posit consensus against military rule, high popular support for democracy, strong civil society, the presence of a strong opposition party, and low levels of cohesion among officers as factors which constrain opportunity. Prior research suggests that when the level of opportunity is high, controlling the state becomes a high-risk/low-reward endeavour, making it likely that officers will allow for a transition to civilian rule. My study contributes to the existing scholarship by using original data gathered through interviews with Egyptian officers, as well as other experts on the Egyptian military, to argue that low consensus against military rule, low support for democracy, and high organizational cohesion are jointly sufficient to produce governing intervention.